Research information management at ISCTE-IUL: the library’s role - Boavida, C. P. (2018)
ISCTE-IUL is a Portuguese public university with approximately 9000 students enrolled in undergraduate (46%) and postgraduate (54%) programs. The Repository of ISCTE-IUL is running since 2007 sustained by an Open Access Policy approved in the same year. In 2013, the current research information system – Ciência-IUL – became interoperable with the Repository bringing new challenges to SID, and allowing work collaboratively with other services to collect information, improve processes, and reduce duplication of efforts. SID seeks to support researchers throughout the research life cycle aiming to raise awareness of the academic community for Open Science best practices.